POLA KALIMAT TUNGGAL PADA TEKS DESKRIPSI SISWA KELAS VII SMP NEGERI I PONDOK KELAPA BENGKULU TENGAH TAHUN AJARAN 2016/2017 - Lilis Suyanti; Supadi Supadi; Marina Siti Sugiyati (Universitas Bengkulu, 2017)
The purpose of this study are to describe the pattern, function, category and the role of single sentence elements in the text description of students in class VII of SMP Negeri 1 Pondok Kelapa Bengkulu Tengah academic year 2016-2017. The method used is qualitative descriptive method. Data and data sources in this study are single sentences in the text description of students in class VII SMP N 1 Pondok Kelapa Bengkulu Tengah academic year 2016/2017. Data analysis technique in this research using permutation technique and paraphrase technique. The results of the research found the following single sentence patterns, S-P, S-P-O, S-P-Pel, S-P-Ket, S-P-O-Ket, S-P-O-Pel, S-Ket-P-O, Ket-S-P, Ket-S-P-O, Ket-S-P-Pel , Ket-S-P-O-Pel, Ket-S-P-O-Ket, S-Ket-P-Pel, S-Ket-P-Ket, Ket-S-Ket-P-Pel, S-P-Pel-Ket, S-Ket-P , S-Ket-Ket, Ket-P-O-Pel, Ket-P-Pel-Ket, Ket-S. Sentence analysis based on function found sentence functions as follows: S, P, O, Ket, Pel. Sentence analysis based on category is found: The function of S are categorized as noun, and noun phrase. The P functions are categorized nouns, noun phrases, verbs, verb phrases, adjective phrases, and numeralia phrases. The O function are categorized as noun, noun phrase and numeralia phrase. Pel functions are categorized nouns, and noun phrases. The function of Ket is categorized as prepositional phrase. The role-based sentence analysis are found as follows: The function S acts as a known, experienced, numbered, actor, gained, and place. Function P acts as an identifier, state, amount, deed, possession, existence, and acquisition. Function O acts as a sufferer, owner, sum, result, and sum. The Pel function acts as the sufferer, owner, number, result, state, and tool. The function of Ket serves as a way, place, time, participant, result, tool, cause, and frequency.